Parental and healthcare provider attitudes towards the Healthy Child Programme in England: a qualitative analysis - Tahmid Rahman; Joseph Freer; Isabella Cordani; Michael Papasavva; Leo Dunkel; Robert Walton; Helen L. Storr; Andrew J. Prendergast; Joanna Orr (BMC, 2024)
Abstract Background The Healthy Child Programme (HCP) in England, delivered by Health Visitors (HV) and Nursery Nurses (NN), aims to assess growth and development in pre-school age children. This qualitative analysis aimed to evaluate the perceptions and experiences of HCP providers and parents located in a London borough. Methods This qualitative analysis is part of a larger study piloting an automated growth screening algorithm in a London borough. We conducted three focus group discussions; two with parents of pre-school children participating in the pilot study, one in English (n = 6) and one in Sylheti (n = 5), and one with HVs and NNs (n = 11). Sampling was purposeful, and written informed consent was obtained. Groups were facilitated by the same bilingual researcher using semi-structured topic guides. Data were analysed using reflexive thematic analysis and assessed for intercoder reliability. Results Three broad themes were identified in the data: (1) lack of clarity around the role of the HV and NN; (2) a lack of resources; and (3) a desire for a preventative service. Underlying these themes was a sense of disempowerment shown by HVs/NNs and parents, as well as systemic issues in terms of the accessibility and practicality of the service. Nevertheless, parents and HVs/NNs all stressed the importance of the service in providing information, reassurance and advice. Conclusions Various challenges prevent the HCP from providing equitable and effective care to every child. However, the service was recognised as very valuable by users and providers despite systemic difficulties.